Aerial Remote Sensing of Aquatic Microplastic Pollution: The State of the Science and How to Move It Forward - Dominique Chabot; Sarah C. Marteinson (Microplastics)
Microplastics (MPs) are pervasive environmental contaminants in aquatic systems. Due to their small size, they can be ingested by aquatic biota, and numerous negative effects have been documented. Determining the risks to aquatic organisms is reliant on characterizing the environmental presence and concentrations of MPs, and developing efficient ways to do so over wide scales by means of aerial remote sensing would be beneficial. We conducted a systematic literature review to assess the state of the science of aerial remote sensing of aquatic MPs and propose further research steps to advance the field. Based on 28 key references, we outline three main approaches that currently remain largely experimental rather than operational: remote sensing of aquatic MPs based on (1) their spectral characteristics, (2) their reduction of water surface roughness, and (3) indirect proxies, notably other suspended water constituents. The first two approaches have the most potential for wide-scale monitoring, and the spectral detection of aquatic MPs is seemingly the most direct approach, with the fewest potential confounding factors. Whereas efforts to date have focused on inherently challenging detection in coarse-resolution satellite imagery, we suggest that better progress could be made by experimenting with image acquisition at much lower altitudes and finer spatial and spectral resolutions, which can be conveniently achieved using drones equipped with high-precision hyperspectral sensors. Beyond developing drone-based aquatic MP monitoring capabilities, such experiments could help with upscaling to satellite-based monitoring for global coverage.